コウイド ホッキョク ニ オイテ コトナル スイブン ジョウケンカ ニ セイイクスル イワダレゴケ ノ セイチョウ パターン - 上野, 健; ウエノ, タケシ; 神田, 啓史; カンダ, ヒロシ; Ueno, Takeshi; Kanda, Hiroshi (2010)
P(論文) イワダレゴケHylocomium splendensは,高緯度北極ツンドラの植生を構成する主要なコケ植物であり,乾燥地から湿地まで幅広い水分環境に生育する.イワダレゴケは,1年ごとに形成される新たな植物体が連続的につながった形態をとるので,年次生長が追跡できる.我々は,生育地の水分条件がイワダレゴケの生長パターンに与える影響を明らかにするために,カナダ北極エルズミア島オーブロヤー湾奥の氷河後退域において,異なる水分条件(湿地: hydric site,中湿地: mesic site,乾燥地: xeric site)に生育するイワダレゴケの成熟期間(growth period)および年間生長量(長さと重さ)を比較した.その結果,イワダレゴケの成熟期間は湿地で1年,中湿地で2年,乾燥地で3年となり,乾いた環境ほど成熟期間が長くなった.年間生長量は,乾いた環境ほど値が小さくなった.これらの結果から,生育地の水分条件は高緯度北極におけるイワダレゴケの生長パターンに大きな影響を与えることが明らかとなった. Hylocomium splendens, a widespread feather moss, is one of the major plant species found in high-Arctic tundra. It occupies a variety of habitats ranging from exposed dry ground to swampy areas. To clarify the effect of the water regime on the growth pattern of H. splendens, the shoot morphology of H. splendens growing in contrasting water regimes, i.e. hydric, mesic and xeric sites, was investigated using retrospective analyses of growth. The derived growth parameters for H. splendens differed considerably among the sites. The growing period at the hydric, mesic and xeric sites was 1 year, 2 years and 3 years, respectively. The annual increments in segment length and biomass were higher with increasing water availability. These results suggest that water regime has a strong influence on the growth pattern of H. splendens in high-Arctic tundra. departmental bulletin paper